Design & Simulation of Rectangular & Circular Patch Antenna with EBG Substrates - Manjit Goyat, Navneet Saroha, (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper presents the design and simulation of rectangular & circular with EBG substrate using High Frequency Structure Simulator (HFSS). The two different configurations of broadband microstrip patch antenna, multistacked rectangular patch antenna & multistacked circular patch antenna are analyzed. Return Loss & Gain are performance parameter. The substrate used in these two configurations is RT Duroid having dielectric constant 2.2. The result calculated is return loss of rectangular patch & circular patch with EBG substrates are -13.98 db & -43.4437 db and gain of rectangular patch & circular patch with EBG substrates are 5.7478 db & 10.4954 db respectively.